MANAJEMEN SERVICE EXCELLENT DALAM MENINGKATKAN TRUST WALI SANTRI TERHADAP PONDOK PUTRI DARUT TAUHID PESANTREN ZAINUL HASAN GENGGONG - Millah, Ziyanatul; Tri Wisudaningsih, Endah; Solehudin, Sollah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Excellent service management has become one of the important efforts to improve service quality in Islamic boarding schools (pesantren). At Pondok Putri Darut Tauhid, Zainul Hasan Genggong Islamic Boarding School, excellent service is implemented through directed planning, clear and friendly administration, and open communication with the guardians of the students. This research aims to analyze the application of excellent service management in enhancing the trust of the guardians of students at Pondok Putri Darut Tauhid, Zainul Hasan Genggong Islamic Boarding School. This research uses a qualitative method with a descriptive approach. Data collection techniques include observation, in-depth interviews, and documentation. Data analysis techniques involve data condensation, data presentation, and conclusion drawing. The validity of the data is tested through credibility, transferability, dependability, and confirmability. The results show that excellent service management at Pondok Putri Darut Tauhid, Zainul Hasan Genggong Islamic Boarding School is implemented through two stages, namely planning and execution. Planning is carried out through monthly meetings that discuss the identification of the needs of the guardians of students, service evaluations, task distribution among the management, provision of facilities and infrastructure, and the establishment of follow-up actions, while implementation is done through friendly administrative services and coordinated communication. The application of excellent service is capable of increasing the trust of the guardians of students, as evidenced by the emergence of trust and confidence in the quality of the boarding school's services, and the implementation of excellent service management provides positive implications for the improvement of service quality, communication effectiveness, and the positive image of the boarding school in society. Thus, structured and continuous excellent service management plays an important role in enhancing the trust of the guardians of students in the boarding school.